The Effect of Maternal Education Level, Family Income, and Maternal Working Time to Basic Vaccine Service on 0-24 Infants in Kupang Regency, East Nusa Tenggara - Frans Salesman (Journal of Health Policy and Management, 2017)
Background: Vaccine stimulates immune system form to the infants to prevent the disease and death. However, the coverage of complete basic vaccine (IDL) has not reached the target yet in Kupang regency, Nusa Tenggara Timur. The study aims to analyze the factors that effect a completeness status of the effect basic vaccine for infants aged 0-24 months at the Oemasi regency, Kupang, East Nusa Tenggara.Subject and Method: The study was observational study using cross-sectional approach. The study was conducted at Oemasi community health center, Kupang regency, Nusa Tenggara Timur. The total of the population were 527 infants aged between 0-24 months. The sample were 60 infants by using quota sampling technique. The independent variable were maternal age, education, and working time, family income, and number of family members. The dependent variable was complete basic vaccine status. The data were collected using questionnaire and analyzed by multiple logistic regression.Result: The maternal education level increased the infants’ possibility to get complete basic vaccine and stasticially significant (OR= 11.47; CI 95%= 1.28  up to 102.63; p= 0.029). Parents’ income increased infants’ possibility to get complete basic vaccine, however it was not statistically signicant. Family member ≥5 people and mother’s working time ≥7 hours/day decreased infants’ possibility to get complete basic vaccine, however it was not statistically significant. Mother’s age did not influence the infants getting complete basic vaccine. Conclusion: mother’s education is a factor which has the strongest effect to increase infants’ possibility to get complete basic vaccine. Keyword: complete basic vaccine, mothers’ education level, family income, family members                                                                                             Correspondence: Frans Salesman. School of Health Polytechnics Citra Husada Mandiri, Kupang, East Nusa Tenggara. Email: franssalesman@gmail.com.Journal of Health Policy and Management (2017), 2(2): 112-116https://doi.org/10.26911/thejhpm.2017.02.02.02